TGF-β1 and CXCL12 modulate proliferation and chemotherapy sensitivity of acute myeloid leukemia cells co-cultured with multipotent mesenchymal stromal cells. Issue 6 (3rd July 2018) - Schelker, Roland Christian; Iberl, Sabine; Müller, Gunnar; Hart, Christina; Herr, Wolfgang; Grassinger, Jochen
ABSTRACT: Objectives: Multipotent mesenchymal stromal cells (MSCs) play a central role within the bone marrow (BM) niche, supporting hematopoiesis via soluble factors like cytokines and chemokines. In our study, we sought to investigate the effect of blocking transforming growth factor beta 1 (TGF-β1) and C-X-C motif chemokine 12 (CXCL12) receptor CXCR4 on acute myeloid leukemia (AML) cells in an MSC co-culture system. Methods: Human MSCs were obtained by BM aspirates and their phenotype and functional properties were confirmed in vitro . Co-cultures of AML cells on MSCs were initiated and compared to those on mouse fibroblasts (MS-5) and liquid cultures. Additionally, the effect of blocking CXCR4 and TGF-β1 on AML cells was tested with and without the addition of cytarabine. Results: MSCs from BM showed a typical phenotype and differentiation pattern. Co-culture of AML cells on MSCs resulted in a significantly higher proliferation capacity than on MS-5 or liquid culture. Blockade of TGF-β1 increased AML cell proliferation and chemosensibility, while the CXCR4 antagonist plerixafor showed anti-proliferative effects and did not change cytarabine-induced cell death compared to control. Discussion: Human MSCs are potent feeder cells, able to maintain AML cells in long-term culture. This favorable co-existence seems to be due in part to molecules important for communication within the niche. Blockade of TGF-β1 and CXCL12 was associated with different effects on AML cell proliferation and chemotherapy resistance. Conclusion: These findings suggest a strong supporting affinity between MSCs and AML cells within the leukemic niche, where TGF-β1 and CXCL12 pathways play an important role.